The Family Context of Autism Spectrum Disorders: Influence on the Behavioral Phenotype and Quality of Life - Smith, Leann E. (2013)
In this review, we report the findings from our longitudinal program of research examining the bidirectional influences of the family environment on the behavioral phenotype of autism, and describe a newly developed family psychoeducation program, titled Transitioning Together, designed to reduce family stress, address behavior problems, and improve the overall quality of life of adolescents with autism and their families. In our search for characteristics of the family environment that influence the behavioral phenotype of adolescents and adults with autism, we focus on both positive dimensions of family life, such as warmth and positive remarks that may promote adaptive behavior in individuals with autism, as well as negative dimensions, such as high levels of criticism that may result in an escalation of behavior problems. We find that high levels of maternal warmth and positive remarks are associated with the abatement of behavior problems over time, while high levels of maternal criticism are associated with increasing levels of behavior problems in adolescents and adults with autism. These patterns of relationships have been replicated in a longitudinal study of families of children and adolescents with fragile X syndrome, and are consistent with other studies examining the impact of the family on the behavior of children with developmental disabilities. These findings suggest that the family environment is an important target for interventions not only to reduce family stress but also to improve the behavioral functioning of children, adolescents or adults with ASD. Building upon a well-developed intervention for families of individuals with psychiatric conditions, we report on the development of Transitioning Together, a psychoeducation program targeted to families with adolescents with autism who are approaching high school exit, a difficult transition stage for individuals with autism that is often marked by negative changes in behavior problems. The 8-week Transitioning Together program involves education on a variety of topics relevant to ASD and guided practice in helping families better manage problem behavior in adolescents with autism. Preliminary data suggest that the program can improve the parent-child relationship and increase parental expressions of warmth. A case study is presented that illustrates how Transitioning Together helps reduce family stress and improve the overall quality of the family environment. We conclude the article with a discussion of directions for future research on best practices in working with families of children, adolescents and adults with autism.